Tasty rewards for ants: differences in elaiosome and seed metabolite profiles are consistent across species and reflect taxonomic relatedness - Konečná, Marie (Jihočeská univerzita, 2023)
The reward for ants in myrmecochory is a nutrient-rich appendage, the elaiosome. This study evaluates the metabolite composition of five groups (i.e. amino acids, fatty acids, organic acids, polyols, and sugars) in elaiosomes compared to the respective seeds. Two plant species from each of the four families (Amaryllidaceae, Boraginaceae, Papaveraceae, and Poaceae) were examined, with each species represented by three populations. The hierarchically designed data enabled the decomposition of variability in metabolite composition at three levels: family, species, and population. Another aspect studied was the consistency of elaiosome metabolite composition across unrelated species from monocotyledonous and dicotyledonous families with different elaiosome origins, which may reflect the convergent evolution of elaiosomes.
Tasty rewards for ants: differences in elaiosome and seed metabolite profiles are consistent across species and reflect taxonomic relatedness
Keywords: Myrmecochory; Convergent evolution; Variation partitioning; Ant-plant mutualism; Seed dispersal; Myrmecochory; Convergent evolution; Variation partitioning; Ant-plant mutualism; Seed dispersal